Colistin resistance in carbapenem resistant klebsiella pneumoniae mediated by chromosomal integration of plasmid DNA (2017)
ABSTRACT : Here we describe the spread of colistin resistance in clinical isolates of carbapenem-resistant Klebsiella pneumoniae in Medellín, Colombia. Among 32 isolates collected between 2012 and 2014, 24 showed genetic alterations in mgrB. Nineteen isolates belonged to sequence type 512 (ST512) (or its single locus variant [SLV]) and harbored an 8.1-kb hsdMSR insertion corresponding to ISKpn25, indicating a clonal expansion of the resistant strain. The insertion region showed 100% identity to several plasmids, suggesting that the colistin resistance is mediated by chromosomal integration of plasmid DNA.